The Effectiveness of Flash Cards in Improving Reading Skills of Elementary School Students - Annisyah; Eny Munisah (Universitas Pendidikan Ganesha, 2025)
The challenge of improving elementary school students' reading skills remains a pressing issue in education. This study aims to evaluate the impact of flash cards on enhancing various dimensions of reading skills, including letter recognition, vocabulary mastery, phonetic ability, and reading comprehension. Using a systematic literature review approach, the research synthesizes findings from eight scientific articles published between 2019 and 2023. The articles were selected based on strict eligibility criteria, including relevance, a citation count exceeding 10, and accessibility. Data were sourced from the Google Scholar database using keywords such as